Explicação passo-a-passo:
a) 2x . 3x =
[tex] {6x}^{2} [/tex]
b) 5y . 3y² =
[tex] {15y}^{3} [/tex]
c) 4xy . x²y³ =
[tex] {4x}^{3} {y}^{4} [/tex]
d) 6ab . (-3ab) =
[tex] { - 18a}^{2} {b}^{2} [/tex]
e) -5ax . (-6ay) =
[tex] { - 30a}^{2}xy[/tex]
f) +9a . ( +5a³) =
[tex] {45a}^{4} [/tex]
g) -10x²y³ . ( -4xyz) =
[tex] {40x}^{3}{y}^{4}z[/tex]
h) -2,3axy . x² =
[tex] {2.3ax}^{3}y[/tex]
i) +6x . x³y² =
[tex] {6x}^{4} {y}^{2} [/tex]
j) +2a . ( -6b) =
[tex] { - 12ab}[/tex]
k) 3x² . 2x³ =
[tex] {6x}^{5} [/tex]
l) -4x . ( -3y) =
[tex]12xy[/tex]
m) -10xy . ( -5x) =
[tex] { 50x}^{2}y[/tex]
n) +7xy . 4y =
[tex] {28xy}^{2} [/tex]
o) ax . ( -8a³) =
[tex] { - 8a}^{4}x[/tex]
Bons estudos